Drivers of foot‐and‐mouth disease in cattle at wild/domestic interface: Insights from farmers, buffalo and lions. Issue 9 (September 2017) - Miguel, Eve; Grosbois, Vladimir; Fritz, Hervé; Caron, Alexandre; de Garine‐Wichatitsky, Michel; Nicod, Florian; Loveridge, Andrew J; Stapelkamp, Brent; Macdonald, David W.; Valeix, Marion
Abstract: Humans live increasingly in the proximity of natural areas, leading to increased interactions between people, their livestock and wildlife. Aim: We explored the role of these interactions in the risk of disease transmission (foot‐and‐mouth disease [FMD]) between cattle and the African buffalo (the maintenance host) and how a top predator, the lion, may modulate these interactions. Location: The interface of Hwange National Park (HNP) and surrounding communal lands, Zimbabwe. Method: We combined a longitudinal serological cattle survey for FMD, GPS‐collar data and cattle owners' interviews during four seasons in 2010–2011. Results: Overall FMD incidence in cattle was low, but showed a peak during the rainy season. The incidence dynamic was significantly explained by cattle incursion into the protected area (i.e., buffer zone of 3 km inside HNP) and not by contacts with buffalo or contacts among cattle. These results suggest that FMD virus either survives in the environment or is transmitted by other ungulate groups or species. The analysis of incursion frequency in the buffer suggests that (1) buffalo and cattle are avoiding each other up to 2 months after one species track and that (2) lions make frequent incursions in the buffer few days to few weeks after buffalo had used it, whereas buffalo did not use areas occupied by lions. Lions could thus reduce the spatio‐temporal overlap between cattle and buffalo in the interface, which could contribute to the low level of FMD incidence. Main conclusions: During the rainy season, traditional herding practices push cattle away from growing crops near villages into the HNP but not during the dry season, suggesting that cattle owners may decide to rely on lower quality resources in the communal land in the dry season to avoid the risks of infection and/or predation in the HNP. This study highlights the complex dynamics that operates at human/livestock/wildlife interfaces.